Age‐related remodelling of the blood immunological portrait and the local tumor immune response in patients with luminal breast cancer. Issue 10 (3rd October 2020) - Berben, Lieze; Floris, Giuseppe; Kenis, Cindy; Dalmasso, Bruna; Smeets, Ann; Vos, Hanne; Neven, Patrick; Antoranz Martinez, Asier; Laenen, Annouschka; Wildiers, Hans; Hatse, Sigrid
Abstract: Objectives: Aging is associated with altered immune function and chronic low‐grade inflammation, referred to as immunosenescence. As breast cancer is an age‐related disease, the impact of aging on tumor immune responses may have important consequences. However, effects of immunosenescence on breast tumor immune infiltration remain largely unknown. Methods: This exploratory study investigated a broad panel of immune/senescence markers in peripheral blood and in the tumor microenvironment of young, middle‐aged and old patients diagnosed with early invasive luminal (hormone‐sensitive, HER2‐negative) breast cancer. In the old group, G8‐scores were computed as a correlate for clinical frailty. Results: Significant age‐related changes in plasma levels of several inflammatory mediators (IL‐1α, IP‐10, IL‐8, MCP‐1, CRP), immune checkpoint markers (Gal‐9, sCD25, TIM‐3, PD‐L1), IGF‐1 and circulating miRs (miR‐18a, miR‐19b, miR‐20, miR‐155, miR‐195 and miR‐326) were observed. Shifts were observed in distinct peripheral blood mononuclear cell populations, particularly naive CD8 + T‐cells. At the tumor level, aging was associated with lower total lymphocytic infiltration, together with decreased abundance of several immune cell markers, especially CD8. The relative fractions of cell subsets in the immune infiltrate were also altered. Clinical frailty was associated with higher frequencies of exhausted/senescent (CD27 − CD28 − and/or CD57 + ) terminally differentiated CD8 + cells in the blood and with increased tumor infiltration by FOXP3 + cells. Conclusion: Aging and frailty are associated with profound changes of the blood and tumor immune profile in luminal breast cancer, pointing to a different interplay between tumor cells, immune cells and inflammatory mediators at higher age. Abstract : In this study, apart from age‐related changes in the immune profile of patients with luminal breast cancer, remarkable frailty‐related changes within the subgroup of older patients were observed. Our data support age‐dependent remodelling of both systemic immunity features and anti‐tumor immune responses.